2003
DOI: 10.1002/poc.600
|View full text |Cite
|
Sign up to set email alerts
|

Effect of carbonyls on the reactivity of polyenes in autoxidation

Abstract: Autoxidation of the biologically active polyenes b-carotene, canthaxanthin, retinyl acetate, methyl retinoate, retinal and 3,7,11,11-tetramethyl-10,15-dioxo-2,4,6,8-hexadecatetraenal (diketoretinal) in solid amorphous films was investigated. The course of the process was followed by electronic and IR spectroscopy. The overall activation energies were obtained. It was shown that insertion in the polyene molecule of a carbonyl group conjugated with polyene chain results in a drastic decrease in the reactivity t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…All mechanisms involve the formation of carotenyl radicals (Car • ) and further peroxy-carotenyl radicals (CarOO • ), the stability of which is directly associated with the extension of the electronic conjugated polyene chain (by resonance). Interestingly, Krasnokutskaya et al [68] demonstrated that insertion in the polyene molecule of a carbonyl group results in a drastic decrease in the reactivity towards molecular oxygen (autooxidation), and, consequently, the formation of CarOO • and Car • radicals (this, during the propagation step of lipid oxidation chain reaction). The authors showed that the reactivity of carboxylated carotenoids decreases, due to the lower initiation and propagation rates in the free radical chain reaction [68].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All mechanisms involve the formation of carotenyl radicals (Car • ) and further peroxy-carotenyl radicals (CarOO • ), the stability of which is directly associated with the extension of the electronic conjugated polyene chain (by resonance). Interestingly, Krasnokutskaya et al [68] demonstrated that insertion in the polyene molecule of a carbonyl group results in a drastic decrease in the reactivity towards molecular oxygen (autooxidation), and, consequently, the formation of CarOO • and Car • radicals (this, during the propagation step of lipid oxidation chain reaction). The authors showed that the reactivity of carboxylated carotenoids decreases, due to the lower initiation and propagation rates in the free radical chain reaction [68].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Krasnokutskaya et al [ 68 ] demonstrated that insertion in the polyene molecule of a carbonyl group results in a drastic decrease in the reactivity towards molecular oxygen (autooxidation), and, consequently, the formation of CarOO• and Car• radicals (this, during the propagation step of lipid oxidation chain reaction). The authors showed that the reactivity of carboxylated carotenoids decreases, due to the lower initiation and propagation rates in the free radical chain reaction [ 68 ]. Notably, ApoC (β-apo-8′-carotenal), a shorter apocarotenoid (C30) with an aldehyde group ( Supplementary Material, Figure S1 ), does not account for such an extended conjugation system as the carboxylated NX, and merely showed equivalent scavenging properties as βC (lacking any conjugated polar group) in liposomal systems here ( Figure 5 A).…”
Section: Discussionmentioning
confidence: 99%
“…β‐Carotene is also, as with most carotenoids, a powerful quencher of singlet oxygen, 1 O 2 84 . Peroxyl radicals add rapidly to polyenes when the resulting C‐radicals are strongly stabilized by resonance (see Figure 12), the rate constants being of the order of 10 4 –10 5 m −1 s −1 85,86 …”
Section: Introductionmentioning
confidence: 99%
“…[84] Peroxyl radicals add rapidly to polyenes when the resulting C-radicals are strongly stabilized by resonance (see Figure 12), the rate constants being of the order of 10 4 -10 5 M -1 s -1 . [85,86] At low oxygen partial pressure, the b-carotene -OOR radical may quickly quench a second peroxyl radical. In fact, addition of dioxygen to b-carotene -OOR occurs reversibly [81] and is characterized by relatively low rate constants.…”
Section: B-carotenementioning
confidence: 99%